2017
DOI: 10.1007/s11892-017-0954-4
|View full text |Cite
|
Sign up to set email alerts
|

The Infamous, Famous Sulfonylureas and Cardiovascular Safety: Much Ado About Nothing?

Abstract: With no dedicated cardiovascular studies to definitively answer this question, observational studies and meta-analyses abound and have reported divergent results, fueling the controversy. Studies that compared SUs to metformin or newer agents, like GLP-1 agonists and SGLT2 inhibitors, suggest a difference in cardiovascular events, yet this is likely the result of beneficial effects of the latter. Studies comparing SUs to other agents have been reassuring. SUs remain a common choice of treatment for patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 72 publications
0
8
0
7
Order By: Relevance
“…Despite more than half a century of clinical use, concerns about their cardiac safety continue to haunt SUs. This is partly because the extensive literature available on their association with cardiovascular events is not only inconsistent but also lacks any conclusive evidence of harm associated with their use as second-line agents [46]. While the cardiac safety profile of SU use from the ADVANCE study and the cardiovascular outcome trial data (CVOT) from the CAROLINA trial were, at best, encouraging from the perspective of most practitioners [40], the influx of more promising cardioprotective evidence for newcomers such as sodium-glucose co-transporter-2 (SGLT-2) inhibitors and glucagon-like peptide-1 receptor (GLP-1) receptor agonists will substantially influence future therapeutic choices, especially for T2D patients with established cardiovascular or renal disease [47,48].…”
Section: Cardiacmentioning
confidence: 99%
“…Despite more than half a century of clinical use, concerns about their cardiac safety continue to haunt SUs. This is partly because the extensive literature available on their association with cardiovascular events is not only inconsistent but also lacks any conclusive evidence of harm associated with their use as second-line agents [46]. While the cardiac safety profile of SU use from the ADVANCE study and the cardiovascular outcome trial data (CVOT) from the CAROLINA trial were, at best, encouraging from the perspective of most practitioners [40], the influx of more promising cardioprotective evidence for newcomers such as sodium-glucose co-transporter-2 (SGLT-2) inhibitors and glucagon-like peptide-1 receptor (GLP-1) receptor agonists will substantially influence future therapeutic choices, especially for T2D patients with established cardiovascular or renal disease [47,48].…”
Section: Cardiacmentioning
confidence: 99%
“…Notably, UKPDS and follow-up studies of its cohort suggested SUs may also have microvascular benefits [50,140]. Because of their robust effects on glycaemic control and established cardiovascular safety, along with the lower cost of SUs compared to other classes of glucose-lowering drugs [141], these agents have a continued role in management of patients with T2D.…”
Section: Sulphonylureasmentioning
confidence: 99%
“…La seguridad cardiovascular de las SU es una cuestión de debate. Las posibles razones para un incremento de riesgo cardiovascular serían que las SU están asociadas al aumento de la proinsulina circulante, que puede elevar los niveles de inhibidor del activador del plasminógeno 1, el principal inhibidor fisiológico de la fibrinólisis, con lo que se aumentaría así el riesgo de aterotrombosis 22 . Otra hipótesis sugiere que las SU pueden inhibir el preacondicionamiento isquémico 10 , un mecanismo cardioprotector en el que periodos cortos de isquemia miocárdica pueden reducir el tamaño de un infarto futuro.…”
Section: ¿Hay Riesgo Cardiovascular Con El Uso De Sulfonilureas?unclassified
“…En cuanto a estudios que evalúan el uso de SU y el riesgo cardiovascular, muchos de estos ensayos analizaron diferentes niveles de control glucémico como la principal intervención para disminuir la enfermedad cardiovascular, y debido a que los grupos de abordaje intensivo en esos estudios tuvieron una mayor exposición a SU, estos estudios también proporcionan evidencia indirecta sobre la seguridad de estos fármacos. La mayoría de estos estudios (Veterans Affairs Diabetes Trial [VADT], ADVANCE, Action to Control Cardiovascular Risk in Diabetes [ACCORD] y UKPDS) demostraron una disminución en las complicaciones microvasculares, pero ninguno de ellos demostró una reducción inequívoca de los resultados macrovasculares 22 . La única excepción en el seguimiento a largo plazo fue el UKPDS, que mostró que los pacientes que fueron originalmente asignados aleatoriamente a recibir tratamiento intensivo mostraron una reducción estadísticamente significativa en el infarto de miocardio en comparación con los asignados a tratamiento conservador, incluso en aquellos en uso de SU o insulina.…”
Section: ¿Hay Riesgo Cardiovascular Con El Uso De Sulfonilureas?unclassified